2021
DOI: 10.3390/molecules26040991
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Nicotinamide-N-Methyltransferase for the Treatment of Metabolic Disorders

Abstract: Nicotinamide-N-methyltransferase (NNMT) is a cytosolic enzyme catalyzing the transfer of a methyl group from S-adenosyl-methionine (SAM) to nicotinamide (Nam). It is expressed in many tissues including the liver, adipose tissue, and skeletal muscle. Its expression in several cancer cell lines has been widely discussed in the literature, and recent work established a link between NNMT expression and metabolic diseases. Here we describe our approach to identify potent small molecule inhibitors of NNMT featuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The key to unlocking this understanding was the first publication of the crystal structure of NNMT co-crystalised with nicotinamide and SAH by Peng and colleagues [200]. The majority of the first small-molecule inhibitors developed were focussed upon targeting NNMT in obesity and alcohol-related fatty liver disease [201][202][203][204][205]. Many of these inhibitors have yet to be tested in in vitro cancer models systems, and questions remain about their selectivity towards NNMT in relation to other methyltransferases as well as their cell permeability.…”
Section: Small-molecule Inhibitors Of Nnmt Activitymentioning
confidence: 99%
“…The key to unlocking this understanding was the first publication of the crystal structure of NNMT co-crystalised with nicotinamide and SAH by Peng and colleagues [200]. The majority of the first small-molecule inhibitors developed were focussed upon targeting NNMT in obesity and alcohol-related fatty liver disease [201][202][203][204][205]. Many of these inhibitors have yet to be tested in in vitro cancer models systems, and questions remain about their selectivity towards NNMT in relation to other methyltransferases as well as their cell permeability.…”
Section: Small-molecule Inhibitors Of Nnmt Activitymentioning
confidence: 99%
“…Several NNMT inhibitors, which are expected to be useful for the treatment of metabolic disorders, have been developed and are available commercially. 16 Our findings suggest that NNMT inhibitors may be effective for the treatment of EC. Moreover, a new biosensor was recently developed for rapid quantification of 1-MNA, which is a metabolite produced by NNMT.…”
Section: Discussionmentioning
confidence: 68%
“…Subsequent studies clearly demonstrated NNMT involvement in fundamental events featuring tumorigenesis, namely, cell proliferation, migration and invasiveness (Figure 2), thus attributing to the enzyme a promising role as a molecular target for effective treatment of these tumors. NNMT 3D structure resolution [11], together with the identification of related kinetic mechanism-of-action [12], have triggered the design, synthesis and validation of a wide range of molecules that seem to act as potent inhibitors of enzyme activity [16][17][18][19][20][21][22][23][24][25][26][27], that could be used as novel anti-cancer therapeutics. Nicotinamide N-methyltransferae (NNMT) involvement in urological tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the enzyme is described to be involved in the biotransformation and detoxification of many xenobiotics [1][2][3], porcine liver NNMT was only described to be active towards pyridine derivatives, such as quinoline, isoquinoline, and 1,2,3,4-tetrahydroisoquinoline, in addition to structural NA analogs, such as thionicotinamide and 3-acetylpyridine [10]. The resolution of tridimensional (3D) structures of purified human recombinant NNMT, together with the detection of the main amino acid residues involved in the catalysis [11], led to the discovery of the kinetic mechanism of NNMT [12], the identification of alternate enzyme substrates [13][14][15], as well as the design and assay of a great number of inhibitors [16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%